2011
DOI: 10.1017/s0954579411000174
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sexual abuse on female development: Lessons from a multigenerational, longitudinal research study

Abstract: This is a report on the research design and findings of a 23-year longitudinal study of the impact of intrafamilial sexual abuse on female development. The conceptual framework integrated concepts of psychological adjustment with theory regarding how psychobiological factors might impact development. Participants included 6- to 16-year-old females with substantiated sexual abuse and a demographically similar comparison group. A cross-sequential design was used and six assessments have taken place, with partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
317
3
27

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(383 citation statements)
references
References 93 publications
(199 reference statements)
21
317
3
27
Order By: Relevance
“…Secure attachment and parental support have been shown to protect against consequences of stress (Beaudoin, Hébert, & Bernier, 2013; Domhardt et al, 2015). Limited-scale longitudinal studies have indicated, however, that 10–20% of asymptomatic children develop symptoms later, an outcome called the sleeper effect (Kendall-Tackett et al, 1993; Putnam, 2003; Trickett, Noll, & Putnam, 2011). Hence, ongoing follow-up assessment in our population is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Secure attachment and parental support have been shown to protect against consequences of stress (Beaudoin, Hébert, & Bernier, 2013; Domhardt et al, 2015). Limited-scale longitudinal studies have indicated, however, that 10–20% of asymptomatic children develop symptoms later, an outcome called the sleeper effect (Kendall-Tackett et al, 1993; Putnam, 2003; Trickett, Noll, & Putnam, 2011). Hence, ongoing follow-up assessment in our population is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, girls are more likely than boys to experience traumatic events that are highly related to dissociation, such as sexual abuse (Bernier, Hebert, & Collin-Vezina, 2013; Collin-Vezina, Daigneault, & Hebert, 2013; Trickett, Noll, & Putnam, 2011). In the current study, we did not examine results by trauma type.…”
Section: Discussionmentioning
confidence: 99%
“…Child maltreatment is associated with short-term and long-term negative consequences. Victims have an increased risk for physical, behavioral, and psychological problems, also up into adulthood (e.g., [8][9][10][11]), and benefit less from treatment compared to non-maltreated individuals [12], leading to high costs for individuals and society. Given the high prevalence rates and serious consequences of maltreatment, effective prevention and reduction of child maltreatment is essential.…”
Section: Child Maltreatmentmentioning
confidence: 99%